Endoscopic Nasopharyngectomy Combined with a Nerve‐sparing Transpterygoid Approach. (16th December 2019) - Geltzeiler, Mathew; Turner, Meghan; Rimmer, Ryan; Zenonos, George; Hebert, Andrea; Snyderman, Carl; Gardner, Paul; Fernandez‐Miranda, Juan; Wang, Eric W.
Abstract : Objectives/Hypothesis: Surgical management of nasopharyngeal tumors has evolved in the endoscopic era. Lateral exposure remains difficult especially near the petrous internal carotid artery and bony Eustachian tube (ET). Our study examines the need to sacrifice the vidian and greater palatine nerves in order to successfully perform en bloc endoscopic nasopharyngectomy. Methods: Four cadaveric specimens (eight sides) were dissected bilaterally using a binarial, extended, endoscopic endonasal approach (EEA). Nasopharyngectomy was completed including an extended transptyergoid approach for resection of the cartilaginous ET at its junction with the bony ET. Dissection was attempted without sacrifice of the vidian or palatine nerves. Results: Successful en bloc nasopharyngectomy combined with a nerve‐sparing transpterygoid approach was achieved in all specimens with successful preservation of the palatine and vidian nerves. The approach provided exposure of foramen lacerum, the petrous carotid, foramen spinosum, and foramen ovale as well as all segments of the cartilaginous Eustachian tube, Meckel's cave and the parapharyngeal carotid. There was no inadvertent exposure or injury of the internal carotid artery. Conclusion: Endoscopic nasopharyngectomy combined with a nerve‐sparing transpterygoid approach allows for en bloc resection of the cartilaginous Eustachian tube and nasopharyngeal contents with broad skull base exposure and preservation of the internal carotid artery, vidian and palatine nerves. Level of Evidence: VI Laryngoscope, 130:2343–2348, 2020